Neutrophil recruitment is inhibited by nicotinamide in experimental pleurisy in mice - Raphael Gomes Ferreira; Tamires Cardoso Matsui; Adriana M. Godin; Lindisley Ferreira Gomides; Pedro Elias Marques; Igor Dimitri Gama Duarte; Gustavo Batista Menezes; Márcio M. Coelho; André Klein (2012)
Several emerging lines of evidence support an anti-inflammatory role for nicotinamide and other vitamin B components. However, the mechanisms underlying their activity remain unclear. In the present study, we investigated the ability of nicotinamide to inhibit both neutrophil recruitment in IL-8-, LTB(4)- or carrageenan-induced pleurisy in mice and the rolling and adherence of neutrophils. Nicotinamide inhibited IL-8-, LTB(4)- and carrageenan-induced neutrophil migration, KC production and carrageenan-induced neutrophil rolling and adherence. We propose that the effects of nicotinamide in inhibiting neutrophil recruitment in carrageenan-induced pleurisy may be due to the ability of nicotinamide to inhibit the action of IL-8 and LTB(4), decrease KC production, and inhibit early events that regulate leukocyte migration from blood vessels into tissue.